KALIGRAFI ISLAM SEBAGAI MEDIA DAKWAH EKONOMI SYARIAH DI ERA MODERN - Sonya Rizla Kusuma (Yayasan Haiah Nusratul Islam, 2025)
Islamic calligraphy, as a fusion of artistic expression and spirituality, holds a vital role in the modern era as a channel for spreading Islamic teachings and advocating Sharia-compliant economic principles. This research investigates the function of Islamic calligraphy as a tool for da'wah within the framework of the contemporary creative economy. Using a qualitative approach and literature analysis, the study underscores how Islamic calligraphy embodies both spiritual and economic values, linking aesthetic appeal with religious messages. Additionally, it explores the potential of Islamic calligraphy to support the growth of Sharia-based creative industries, highlighting its significance in empowering Muslim communities economically. By harmonizing artistic, economic, and religious elements, Islamic calligraphy not only safeguards cultural heritage but also acts as a driving force for advancing Sharia-compliant economic practices in today's world.